PENINGKATAN HASIL BELAJAR LARI ESTAFET DENGAN MENGGUNAKAN MODIFIKASI PERMAINAN PIENJONG PADA SISWA KELAS 6 SDN 1 KEMIRIOMBO KECAMATAN GEMAWANG KABUPATEN TEMANGGUNG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve learning outcomes relay with modifications pienjong game on the Grade 6 students at SDN 1 Kemiriombo, District Gemawang, Regency Temanggung. This study uses action research implementation consists of two cycles. Each held one meeting cycle consists of four stages, namely: planning, implementation, observation, and reflection. The instrument used in this study is the test performance of students, student observation sheet, and a written test. Based on the results, the percentage of mastery learning outcomes in cycle 1, psychomotor aspects of 43.7%, 93.7% affective aspects, cognitive aspects of 18.7%, and mastery learning students is 62.5% of the total number of students. In cycle 2 psychomotor aspects of 93.7%, 100% affective aspects, cognitive aspects of 43.7%, and mastery learning students is 81.3% of the total number of students. Present study showed an increase in mastery learning students by 18.8%, from 62.5% in Cycle 1 to 81.3% in cycle 2. Based on the above results, it was concluded that the modification of the game pienjong relay in learning can improve learning outcomes of students grade 6 SDN 1 Kemiriombo.